Development of chondrocyte‐laden alginate hydrogels with modulated microstructure and properties for cartilage regeneration. (30th December 2022) - Lertwimol, Tareerat; Sonthithai, Pacharapan; Hankamolsiri, Weerawan; Kaewkong, Pakkanun; Uppanan, Paweena
Abstract: Alginate hydrogel is an attractive biomaterial for cell microencapsulation. The microarchitecture of hydrogels can regulate cellular functions. This study aims to investigate the applicability of sodium citrate buffer (SCB) as a culture medium supplement for modulating the microstructure of alginate microbeads to provide a favorable microenvironment for chondrogenic induction. The chondrocyte‐laden microbeads, with and without TGF‐β3 incorporation, were produced through an encapsulator. The obtained small‐sized microbeads ( 300 μm) were exposed to a treatment medium containing SCB, composed of varied concentrations of sodium citrate (1.10–1.57 mM), sodium chloride (3.00–4.29 mM), and ethylenediaminetetraacetic acid (0.60–0.86 mM) to partially degrade their crosslinked structure for 3 days, followed by culture in a normal medium until day 21. Scanning electron microscope micrographs demonstrated a loose hydrogel network with an enhanced pore size in the SCB‐treated microbeads. Increasing the concentration of SCB in the treatment medium reduced the calcium content of the microbeads via a Na + /Ca 2+ exchange process and improved the water absorption of the microbeads, resulting in a higher swelling ratio. All the tested SCB concentrations were non‐cytotoxic. Increases in aggrecan and type II collagen gene expression and their corresponding extracellular matrix accumulation, glycosaminoglycans, and type II collagen were vividly detected in the TGF‐β3‐containing microbeads with increasing SCB concentrations in the treatment medium. Our findings highlighted that the combination of SCB treatment and TGF‐β3 incorporation in the chondrocyte‐laden microbeads is a promising strategy for enhancing cartilage regeneration, which may contribute to a versatile application in cell delivery and tissue engineering.